Epidemiology of Methicillin-Resistant Staphylococcus aureus in Slovakia, 2020 - Emergence of an Epidemic USA300 Clone in Community and Hospitals - Tkadlec, Jan; Le, Anh Vu; Brajerova, Marie; Soltesova, Anna; Marcisin, Jozef; Drevinek, Pavel; Krutova, Marcela (Microbiology spectrum, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a leading cause of health care-associated infections. Additionally, over the decades, the spread of community-associated (CA-MRSA) clones has become a serious problem. The aim of this study was to gain data on the current epidemiology of MRSA in Slovakia. Between January 2020 and March 2020, single-patient MRSA isolates (invasive and/or colonizing) were collected in Slovakia from hospitalized inpatients (16 hospitals) or outpatients (77 cities). Isolates were characterized via antimicrobial susceptibility testing, spa typing, SCCmec typing, the detection of mecA/mecC, genes coding for Panton-Valentine leukocidin (PVL), and the arcA gene (part of the arginine catabolic mobile element [ACME]). Out of 412 isolates, 167 and 245 originated from hospitalized patients and outpatients, respectively. Inpatients were most likely older (P < 0.001) and carried a strain exhibiting multiple resistance (P = 0.015). Isolates were frequently resistant to erythromycin (n = 320), clindamycin (n = 268), and ciprofloxacin/norfloxacin (n = 261). 55 isolates were resistant to oxacillin/cefoxitin only. By clonal structure, CC5-MRSA-II (n = 106; spa types t003, t014), CC22-MRSA-IV (n = 75; t032), and CC8-MRSA-IV (n = 65; t008) were the most frequent. We identified PVL in 72 isolates (17.48%; 17/412), with the majority belonging to CC8-MRSA-IV (n = 55; arcA+; t008, t622; the USA300 CA-MRSA clone) and CC5-MRSA-IV (n = 13; t311, t323). To the best of our knowledge, this is the first study on the epidemiology of MRSA in Slovakia. The presence of the epidemic HA-MRSA clones CC5-MRSA-II and CC22-MRSA-IV was found, as was, importantly, the emergence of the global epidemic USA300 CA-MRSA clone. The extensive spread of USA300 among inpatients and outpatients across the Slovakian regions warrants further investigation. IMPORTANCE The epidemiology of MRSA is characterized by the rise and fall of epidemic clones. Understanding the spread, as well as the evolution of successful MRSA clones, depends on the knowledge of global MRSA epidemiology. However, basic knowledge about MRSA epidemiology is still fragmented or completely missing in some parts of the world. This is the first study of MRSA epidemiology in Slovakia to identify the presence of the epidemic HA-MRSA clones CC5-MRSA-II and CC22-MRSA-IV and, importantly and unexpectedly, the emergence of the global epidemic USA300 CA-MRSA clone in the Slovakian community and hospitals. So far, USA300 has failed to spread in Europe, and this study documents an extensive spread of this epidemic clone in a European country for the first time.
Keywords: Hospitals; MRSA; PVL; CA-MRSA; mikrobiální testy citlivosti; nemocnice; spa typing; Slovakia; lidé; Cross Infection; methicilin rezistentní Staphylococcus aureus; Microbial Sensitivity Tests; stafylokokové infekce; USA300; infekce spojené se zdravotní péčí; Staphylococcal Infections; Slovenská republika; Methicillin-Resistant Staphylococcus aureus; Humans